O discurso do professor sobre aluno-problema : uma transgressão bem dita - Silva, Nilzete Cruz (2014)
The objective of this thesis is to deal with the linguistic transgression in the discourse of teachers about the student with bad behavior Aluno-Problema (AP) , analyzing how that discourse realizes the teacher s attitudes in favor of AP. A ducrotian principle states that language is argumentative, and expressed in speeches in the form of normative arguments (therefore), because it may follow the linguistic system pattern, and of transgressive arguments (however), because it may transgress this same pattern. Another principle is that a lexical item has its meaning in it (Ducrot, 1990) that leads to possibilities for continuation in the speech and prevents several other continuations. The expression AP linguistically guides the discourse to normative threads of the type AP therefore rejection and prevents threads of the type AP however aid: it is difficult to deal with AP; they are not well accepted in school environments. That is a pattern. The discourses of the teachers interviewed on the AP s behavior should follow the pattern of the corpus of this work, in relation to linguistic guidelines of the expression AP, which would be AP therefore neg-aid. In the analyzed discourses we have found, on the contrary, a transgression of the pattern, i.e. AP however aid. We believe that, to accomplish this transgression, the teacher is, in fact, following a pattern that refers to the guidelines of the lexical item teacher. In other words, in the Language, the lexical item teacher guides for "one who helps" "one who understands" "one who accepts". Thus, the transgression is justified to follow the "duties" of this profession. In this sense, to violate a pattern, to follow another one, becomes beneficial to the AP. The title of our work is justified along these lines. An important aspect of an argumentative discourse meaning is the relationship among normative argumentative threads and transgressive ones, that constitutes it. Thus, we analyzed those relations, searching for the meaning of those words (therefore and however), in a corpus that consists of 7 interviews/speeches of teachers who work at two elementary schools of Conceição do Coité/Bahia. The work is based on the Theory of Argumentation within Language (ANL) defended by Oswald Ducrot, and J. S. Anscombre, and on its current form, the Theory of Semantic Blocks (TBS), developed by Marion Carel and Oswald Ducrot. The choice of this theoretical approach is due to the fact that the ANL/TBS has as most important principles, the assumptions that the arguments are in the language, but not outside it, and that the meaning of a linguistic entity is composed by other speeches that the entity mentions.